Review: Modern Extraction Methods for Extraction Proanthocyanidins from Natural Products - Li’izzah Diana Manzil; Aditya Sindu Sakti (Faculty of Medicine, Diponegoro University, 2026)
Proanthocyanidins are widely distributed in many plant species and are recognized for their beneficial health effects, particularly their antioxidant and anti-inflammatory activities. This literature review aims to evaluate modern extraction techniques used to isolate proanthocyanidins from natural sources. Conventional methods, such as maceration and Soxhlet extraction, often result in reduced yields because proanthocyanidins are heat-sensitive and susceptible to oxidation. To address these limitations, this review explores alternative modern extraction approaches. Relevant peer-reviewed articles were identified through a comprehensive search of five academic databases: ScienceDirect, PubMed, Google Scholar, NCBI, and BMC. The modern extraction techniques examined include Ultrasound-Assisted Extraction (UAE), Microwave-Assisted Extraction (MAE), Enzyme-Assisted Extraction (EAE), and Pressurized Liquid Extraction (PLE). Evidence from 23 selected studies shows that UAE and MAE are among the most effective and efficient methods for extracting proanthocyanidins from natural matrices. These findings underscore the potential of modern extraction technologies to improve both the yield and quality of proanthocyanidins, supporting their broader application in pharmaceutical and nutraceutical fields.